Explaining and benchmarking corporate bond returns - Gjergji Cici; Scott Gibson; Rabih Moussawi (University of Cologne, Centre for Financial Research (CFR), 2017)
We evaluate how different betas and characteristics related to default, term, and liquidity risk fare against one another in explaining the cross-section of corporate bond returns. We find that characteristics-credit rating, duration, and Amihud illiquidity measure-fare better. Yields add incremental explanatory power. Consistent with yields providing a timelier assessment of default risk than ratings, bonds with higher yields but similar credit ratings, durations and Amihud measures experience more subsequent ratings downgrades, fewer upgrades, and a higher frequency of defaults. Based on our findings, we present characteristic portfolios that can be used to benchmark individual bond and portfolio returns.
Keywords: 330